Intermediate uveitis and Lyme borreliosis. - Breeveld, J (1992)
A case of chronic intermediate uveitis and associated classic snowbanking (pars planitis) with severe cystoid macular oedema probably due to Lyme borreliosis is reported. Despite a disease duration of 10 years the patient's ocular symptoms and visual acuity responded promptly to intravenous ceftriaxone treatment. This case demonstrates that periodic reevaluation of patients with intermediate uveitis is necessary to obtain a specific diagnosis which may include Lyme borreliosis.